Language games and Southeast Asia-United States relations, 1954-2006 - Misalucha, Charmaine Galos (2009)
Narratives of Southeast Asia-US relations usually depict the flow of power as unidirectional. In most instances, the relationship is seen as being led by the US, and the Southeast Asian states take on the role of free riders. In other accounts, power is held by the small Southeast Asian states when they are able to “pull” the US into the security architecture of the region. However, given that the flow of power is indeed unidirectional, what explains why sometimes it is the US that seems to shape, influence, or steer the relationship, while at other times it is the Southeast Asian nations? The relationship has also been described as following certain types of rule or order: sometimes it is described as hegemony, while at other times it is characterized by hierarchy. What explains this assortment of international orders? Moreover, what makes one type of rule hold in a particular time period?